COMMUNITY EMPOWERMENT THROUGH STUDENT WORK LECTURES (KKM) IN SUMURANJA VILLAGE, PULO AMPEL - Fatari, Fatari; Sumarsih, Rani Sri; Hendrawati, Sulkiah; Sabrawijaya, Sabrawijaya; Suadma, Udin; Muliyani, Triya; Elvitra, Dhito D; Suanggi, Anggi (Yayasan Education and Social Center, 2025)
Student Work Lecture (KKM) is a form of community service implemented by students as part of the Tri Dharma of Higher Education. The program focuses on empowering communities through the transfer of knowledge, skills, and direct mentoring based on local needs. This article aims to describe the role and contribution of KKM in enhancing community empowerment, particularly in the economic, educational, and social sectors. The research method employed is descriptive qualitative, utilizing documentation from KKM activities conducted in one of the assisted villages. Findings indicate that active participation of students in various programs such as training, workshops, and community mentoring has brought positive changes to community behavior and increased local capacity. KKM not only strengthens community skills but also fosters collaboration between higher education institutions and local stakeholders, creating sustainable benefits for community development.